Visual preference of urban riverfront among Kuala Lumpur residents - Hilaluddin, Raudhah (2017)
Rapid urbanization and population growth of Kuala Lumpur city have drastically changed the relationship between the society and the river. It is unfortunate that for years, the river has been transformed into a concrete drainage and lost its identity. This is worsened by the lack of aesthetic value and the absence of social activities along the riverside area. ‘River of Life’ project initiated by the Kuala Lumpur City Hall is an ambitious attempt to revitalise the Kuala Lumpur riverfront. The aim is to improve the city image and to create opportunities for development close to the city centre. Since the proposed riverfront involves the making of public spaces, the public preferences need to be considered in developing effective riverfront development. This study was carried out to determine the visual preference of Kuala Lumpur riverfront as perceived by the residents of Kampung Bharu, Brickfields, Chow Kit and Titiwangsa. Visual Preference Survey was conducted with 304 respondents. The survey includes a photo-questionnaire and close-ended questions to measure their preference for scenes typical of the riverfront for future riverfront of Kuala Lumpur and their perceptions of attractive elements that should characterise the river. The study found that the respondents preferred the organised natural setting along the riverfront. They would like to see an expansion of newer areas which will provide water connected activities, higher pedestrian volume and increased amenities along the riverside of Kuala Lumpur. The findings could be a guide for the architects to design the future Kuala Lumpur riverfront that suits the character of the city. It could also improve the visual image and attractiveness of the area for enhanced public activities.